DAMPAK SOSIAL EKONOMI ASURANSI SYARIAH TERHADAP PERLINDUNGAN KEUANGAN KELUARGA: PERSPEKTIF MULTIDISIPLINER - Sry Lestari; Yuni Armayanti (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2025)
Economic uncertainty, increasing household financial risks, and the limited availability of Sharia-compliant financial protection instruments pose significant challenges for Muslim families. Although Islamic insurance has grown rapidly, comprehensive studies examining its socio-economic impact on family financial protection remain limited. This study aims to analyze the socio-economic impact of Islamic insurance on family financial protection using a multidisciplinary approach. A qualitative descriptive method was employed through literature review and in-depth interviews, with thematic data analysis integrating economic, social, and maqashid al-shariah perspectives. The findings reveal that Islamic insurance plays a significant role in mitigating financial risks, strengthening household economic resilience, and fostering social solidarity grounded in Islamic values. The multidisciplinary approach highlights that Islamic insurance functions not only as a financial instrument but also as a social and normative mechanism. The study implies the need to enhance Islamic insurance literacy, develop more inclusive takaful products, and integrate Islamic insurance into sustainable family financial protection policies.